FRI0020 BMP-2 and TGF-B Inhibit IL-34 Expression in Rheumatoid Arthritis Synovial Fibroblasts. (15th July 2016) - Chemel-Mary, M.; Legoff, B.; Maugars, Y.; Heymann, D.; Verrechia, F.
Abstract : Background: Interleukin-34 (IL-34) is a pro-osteoclastogenic cytokine, up-regulated by pro inflammatory cytokines, with a recently described role in rheumatoid arthritis (RA). TGF-b and BMP-2 are two members of the TGF-b family, whith an opposit role to the pro-inflammatory cytokines and that are also involved in rheumatoid synovitis. Objectives: The present study aimed to assess the IL-34 expression in response to two members of the TGF-b family, TGF-b1 and BMP-2, in synovial fibroblasts from RA patients. Methods: The IL-34, TGF-β1 and BMP-2 productions were measured in synovial fluids by ELISA. The IL-34 mRNA levels were quantified by qPCR in human synovial fibroblasts and murine mesenchymal stem cells (MSCs). Pharmacological inhibitions were used to determine the involvement of ALK1 and ALK5 downstream TGF-b1 and BMP-2. Results: IL-34, TGF-b1 and BMP-2 were expressed in synovial fluids from RA patients. We found a significant correlation between IL-34 and TGF-b1 expressions. Levels of both IL-34 and TGF-b1 were thus correlated with the total leukocyte counts in the synovial fluids. TGF-b1 and BMP-2 decreased Il-34 expression in the synovial fibroblasts or in mMSC in a dose/time dependent manner through respectively ALK5 and ALK1 pathways. In addition, TGF-b1 antagonized TNFa-induced IL-34 gene expression. Conclusions: This work identifies TGF-b1 and BMP-2 as potent inhibitors of IL-34 expression in RA synovial fibroblasts. These cytokines, as upstream inhibitors of IL-34, may thus contribute to antagonize inflammation and bone erosions in RA. References: Klareskog L, Catrina AI, Paget S. Rheumatoid arthritis. Lancet. 2009;373:659–72. Lin H, Lee E, Hestir K, Leo C, et al. Discovery of a cytokine and its receptor by functional screening of the extracellular proteome. Science. 2008;320:807–11. Baud'huin M, Renault R, Charrier C, et al. Interleukin-34 is expressed by giant cell tumours of bone and plays a key role in RANKL-induced osteoclastogenesis. J Pathol. 2010;221:77–86. Chemel M, Le Goff B, Brion R, et al. Interleukin 34 expression is associated with synovitis severity in rheumatoid arthritis patients. Ann Rheum Dis. 2012;71:150–4. Pohlers D, Beyer A, Koczan D, et al. Constitutive upregulation of the transforming growth factor-beta pathway in rheumatoid arthritis synovial fibroblasts. Arthritis Res Ther. 2007;9:R59. Disclosure of Interest: None declared